Statistics and Analysis of the Relationship between Strength and Age of Coral Concrete - Bo Liang; Lan Rao; Yun Zheng (Advances in Civil Engineering)
In this study, based on the experimental results of this study and from the previous research, it is concluded that the compressive strength of coral concrete at 3, 7, 14, 21, 60, and 90 days reaches about 71%, 84%, 92%, 96%, 104%, and 110% of that at 28 days, respectively, indicating that the early strength development of coral concrete is significantly faster than that of ordinary concrete but slower in the later stage. A new model to characterize the strength-age relationship of coral concrete is proposed in this study, which is in good agreement with the experimental result, but for the long-term strength prediction of coral concrete in actual engineering, it is recommended to adjust the prediction results according to the environment and working conditions of coral concrete, and the adjustment coefficient could be approximately taken as 0.88. In addition, the effects of water-binder ratio (w/b), total dosage of cementitious materials (b), supplementary cementitious material (SCM) content, and aggregate properties, on the age strength development of coral concrete are studied.